Principles and approaches in Hans Eysenck's personality theory: Their renaissance and development in current neurochemical research on individual differences. (1st February 2021) - Netter, Petra; Hennig, Juergen; Munk, Aisha Judith
Abstract: The paper tried to demonstrate by selected experiments, how principles and approaches applied by H.J. Eysenck's exploration of individual differences are represented in current neurochemical personality research (NCPR) The principle of dimensionality, extrapolating behaviour from psychopathology to the range of healthy persons could be shown to be also valid for differences in hormone responses to serotonergic, dopaminergic and noradrenergic drug stimulation. Eysenck's approach to use drugs as research tools is verified by neurotransmitter challenge tests suitable to manifest the neurochemical basis of behaviour, e.g. the role of dopamine and noradrenaline for different aspects of arousal; and by inducing personality related behaviour, e.g. aggression, by manipulating serotonin supply. Constant refinement of theory emphasized by Eysenck is represented in NCRP by analysing constellations of responses to different drugs within and between different transmitter systems and by combinations of response parameters resulting in discrimination of neurochemically defined subtypes or clusters of personality dimensions. Finally the inverted U-shape function demonstrated in Eysenck's drug postulate could be further developed and explained by underlying neurochemical mechanisms. NCRP can thus help to understand the relationship between personality and psychiatric disorders, to disclose transmitter related clustering and discrimination of personality dimensions and to detect new neurochemical mechanisms.